Single-atom tungsten doping induced chemical–electrochemical coupled pathway on Ni(OH) 2 enables efficient urea electrooxidation - Cai, Lebin; Bai, Haoyun; Li, Jilong; Xie, Feng; Jiang, Kang; Lu, Ying-Rui; Pan, Hui; Tan, Yongwen (Energy & environmental science, 2025)
The electrocatalytic urea oxidation reaction (UOR) has emerged as a promising alternative to the oxygen evolution reaction (OER) for wastewater recycling and energy recovery. However, the traditional UOR pathway on NiOOH surface is hindered by the rate-limiting desorption of *COO and the competition between the UOR and OER. In this study, we propose a chemical–electrochemical coupled pathway for the direct UOR, achieved through the construction of a single-atom W-doped nanoporous P–Ni(OH) 2 catalyst (np/W–P–Ni(OH) 2 ). Specifically, the np/W–P–Ni(OH) 2 catalyst exhibits exceptional UOR performance with an ultralow potential of 1.28 V vs. RHE to reach 10 mA cm −2 and a high UOR selectivity exceeding 90% across the entire potential range. A collection of in situ spectroscopies and theoretical calculations reveal that single-atom W dopants not only accelerate the formation of Ni(OH)O active intermediates by modulating the O charge in the lattice hydroxyl, but also lower the energy barrier of the proton-coupled electron transfer step and the cleavage of the C–N bond, thus realizing the highly efficient UOR.